(untitled) (Sociologisk Forskning, 2009)
Divorces and separations: the impact of role specialisation and equality At the same time as women made their large scale entrance on the labour market divorce rates increased in most western societies. This combination of societal trends was widely understood from the perspective of the specialization and trading model, which implies undermined marital stability through decreasing interdependency between husband and wife. We argue the need to acknowledge the new roles, and perceptions of these roles, men and women have in order to explain differences in separation and stability among couples. When both partners are expecting to be in paid labour and share housework responsibilities, specialisation could actually be a risk factor for cohabitational dissolution. This article uses a ten year longitudinal database of all Swedish cohabiting first time parents in 1993. The analyses generally support what could be labelled a role balance model on separation rather than the specialization model. Looking at the father’s participation in childcare this was quite clear, where the man’s outtake of parental leave for the first child was shown to be related to reduced hazards of separation. In the same way equal distribution of the household labour market incomes between the partners was related to lower hazards of separation.